Impacts of soil compaction on emitter performance in sub-surface drip irrigation system - Bammami, Mohammed Isa (2015)
This research focuses the effect of soil compaction on performance of the Subsurface Drip Irrigation (SDI) system; since the emitters in this system are buried, by operating heavy farm machineries on the field, compaction is bound to occur and secondly finding methods of improving emitter performance, mainly in circumstances where the soil is compacted. Subsurface drip irrigation provides the required amount of water and fertilizer, directly onto the plant root zone with a high efficiency. However, SDI Mperformance is often affected by poor distribution uniformity of emitters. Therefore, the aim of this study is to investigate the variation of the emitters’ discharge rate and wetting patterns on SDI system performance due to soil compaction. To achieve this objective an experiment consisting of an air tank, water reservoir, digital flow meter,digital penetrologger, pressure gauge, emitters with three discharge rates of 2, 4, and 8 L/hr, three different soil samples loosely packed in lysimeters were carried out. Emitters were buried at a depth of 10 cm, 20 cm, and 30 cm in the lysimeters. External load was applied onto the soil srface while monitoring the discharge rate of emitters using the digital flow meter. The soil cone index was determined at different soil depth using the digital penetrologger. Data collected from these two devices were then used to establish a relationship between soil cone index and emitter discharge coefficient. Using the relationship developed, by imputing cone index (MPa) into the equation; the decrease in emitter discharge rate q can be predicted. A significant negative correlation was found between the cone index and emitter discharge rate. For all experiments using three soil samples, a substantial decrease in emitter discharge and emitter wetting diameter was observed. A decrease of 60% to 100% in the emitter discharge rate depending on the soil exposure to loading was recorded and 15% to 50% decrease in wetting diameter were recorded depending on the soil type and decrease in emitter discharge rate. Data obtained from the experiment was further fed into the HYDRUS software to simulate the wetting pattern of the emitters before and after compaction. A significant decrease in emitter discharge rate with the increase in a soil cone index was observed and consequently, a decrease in emitter wetting diameter. This study has shown a greater effect of compaction on emitter discharge rate compared to emitter wetting diameter. To ameliorate the effect of compaction on the emitter performance,the emitter operating pressure was increased from 1 bar to 1.5 bars; even at higher soil cone index, emitter discharge rate increases with the increase of operating pressure. Emitters buried at deeper lateral depth, have shown a higher resistance to soil compaction. In conclusion, this study has shown that emitter discharge rate and wetting diameter decreases with the increase in soil cone index and encourages deeper lateral depth and higher operating pressure depending on a soil cone index.